Politeness speech act in the movie character “Toni Erdmann" by Maren Ade: A Pragmatic study and its relevance in learning German at school - Arif Hifzul; Zainal Rafli; Nuruddin Nuruddin (English, 2020)
In communicating activities, politeness in a language is an important aspect to consider and a part that must be owned by everyone. The purpose of this study is to be able to describe the politeness of the speech spoken by the characters in the movie "Toni Erdmann" by Maren Ade and their relevance in learning German at school. This research uses the descriptive qualitative method. Based on the results of data analysis, there are various forms of the politeness speech act in the film "Toni Erdmann" by Maren Ade. Compliance occurs in the maxim of wisdom, a maxim of generosity, a maxim of praise or appreciation, a maxim of simplicity, a maxim of agreement, and a maxim of sympathy or sympathy. The results of this study can be used as new insights and pragmatic learning concepts. This research is expected to provide positive input for German learning activities, to increase knowledge in aspects of language and to improve language skills.